Nutritive properties of commercially available Pinangat from Camalig, Albay - Castro, Celeste Arboleda; Rumbaoa, Rowena Grace O. (2009.)
ABSTRACT Pinangat is an economically important product of Camalig, Albay primarily made from taro leaves and coconut milk. In an effort to understand the nature of pinangat as a food, this study aimed to determine the nutrient content of commercially available pinangat and its relation to health. Chromatographic, gravimetric, spectrophotometric, and titrimetric methods of analyses were used to determine the amounts of the nutrients per 100 g of pinangat. Among the micronutrients, fat is the most abundant, comprising 22.20 g + 0.13 of pinangat. Most of this fat is in the saturated form, primarily composed of lauric, myristic and palmitic fatty acids. Sterols, determined as cholesterol, are present at 20.00 mg + 0.02. Protein in pinangat was quantified as 4.48 g + 0.20. Dietary fiber contributes 3.85 g + 0.07 to the total carbohydrates, wherein available carbohydrates contribute 0.32 g + 0.02. Although preformed vitamin A is not detectable in pinangat, vitamin C content is determined as 3.45 mg + 0.07 per 100 g. Pinangat has 141.50 mg + 0.70, 1.50 mg, and 396.00 mg + 1.41 calcium, iron and sodium, respectively. Pinangat has a caloric value of 219 kcal per 100 g, and is a good source of calcium, iron and dietary fiber. However, it also has high fat and sodium content, intake of which should be regulated. It is recommended that further studies on the amino acid content, phytosterols, protein quality and other minerals and vitamins be done on pinangat to provide a more comprehensive understanding of its nutritive properties.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food -- Composition; Pinangat